THE DEVELOPMENT OF LEARNING ACTIVITIES USING A GAME-BASED LEARNING APPROACH TO ENHANCE ANALYTICAL THINKING SKILLS OF GRADE 9 STUDENTS - Kaewmamuang, Patcharin; Kaewmamuang , Thapakorn (Journal of MCU Nakhondhat, 2025)
The research aimed to 1) Develop learning activities 2) Compare the academic achievement before and after learning of students who learned with activities 3) Compare the analytical thinking skills of students who learned with activities 4) Study the opinions of Mathayom 3 students on the activities. This was a quantitative research. The sample group was Mathayom 3 students of Nawaminthrachinuthit Triam Udom Suksa Nomklao School, Semester 1, Academic Year 2024, totaling 83 people from 3 classrooms by simple random sampling using the classroom as the sampling unit. The research instruments were 1) Structured interview form for interviewing experts 2) Learning activity plan using game-based learning process in Science 3) Activity quality assessment form 4) Academic achievement test 5) Analytical thinking skill test 6) Student opinion questionnaire The statistics used in data analysis were mean, standard deviation (S.D.) and score comparison using t-test for Dependent Samples. The results of the research found that 1) The quality of learning activities using game-based learning process Very good quality 2) Academic achievement of students who studied with learning activities using game-based learning process had higher scores after studying than before studying with statistical significance at the .01 level. 3) Analytic thinking skills of students who studied using game-based learning process had higher scores after studying than before studying with statistical significance at the .01 level. 4) Students’ opinions towards learning activities were at the highest level.